Pengaruh Komite Audit Dan Tenur Audit Terhadap Integritas Laporan Keuangan (Studi Empiris Di Sektor Infrastruktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2021-2023) - Fany Alvionita; Tiolina Evi Pardede (Jurnal Akuntansi Manajerial, 2026)
This study aims to examine the effect of the audit committee and audit tenure on the integrity of financial statements. The audit committee is measured by the number of audit committee members in each company, while audit tenure is measured by the length of the engagement between the auditor and the client company. The integrity of financial statements is proxied by accrual conservatism (ConAcc) based on the model developed by Givoly, D., & Hayn, C. (2002), which is calculated as the difference between Net Income and Operating Cash Flow. The conservatism value is then classified into two categories: a value of 1 for a negative difference indicating conservative financial reporting, and 0 for a positive difference indicating non-conservative financial reporting. The sample was determined using a purposive sampling technique, resulting in 162 firm observations over a three-year research period. Hypothesis testing was conducted using logistic regression analysis to examine the relationship between the independent variables and the integrity of financial statements. The results indicate that the audit committee and audit tenure have a significant effect on the integrity of financial statements. These findings contribute to the corporate governance literature and provide practical implications for regulators and stakeholders in enhancing the reliability and quality of financial reporting.